Tachymenis peruviana Wiegmann, 1834 (Serpentes, Dipsadidae) in Argentina: Geographic distribution and a new province record - Gallardo, Gabriela Alejandra (2019)
Tachymenis peruviana Wiegmann, 1834 (Serpentes, Dipsadidae) is known from Peru, Bolivia, northern Chile and northwestern Argentina.  In northwestern Argentina, the species is distributed from Jujuy to Catamarca province. In this study, we present the accurate distribution of the species in Argentina and the first records from La Rioja province, at 2000 and 3000 m a.s.l. in the Famatina region, extending the known distribution to the southwest.